Safety and efficacy of inebilizumab for the treatment of neuromyelitis optica spectrum disorder: end-of-study results from the open-label period of the N-MOmentum trial - Cree, Bruce A C; Kim, Ho Jin; Weinshenker, Brian G; Pittock, Sean J; Wingerchuk, Dean M; Fujihara, Kazuo; Paul, Friedemann; Cutter, Gary R; Marignier, Romain; Green, Ari J; Aktas, Orhan; Hartung, Hans-Peter; et al. (The Lancet. Neurology, 2024)
BACKGROUND: Inebilizumab, an anti-CD19 B-cell-depleting antibody, demonstrated safety and efficacy in neuromyelitis optica spectrum disorder in the randomised controlled period of the N-MOmentum trial. Here, end-of-study data, including the randomised controlled period and open-label extension period, are reported. METHODS: In the double-blind, randomised, placebo-controlled, phase 2/3 N-MOmentum trial, adults aged 18 years and older with an neuromyelitis optica spectrum disorder diagnosis, Expanded Disability Status Scale score of 8·0 or less, and history of either at least one acute inflammatory attack requiring rescue therapy in the past year or two attacks requiring rescue therapy in the past 2 years, were recruited from 81 outpatient specialty clinics or hospitals in 24 countries. Eligible participants were randomly assigned (3:1), using a central interactive voice system or interactive web response system, and a permuted block randomisation scheme (block size of 4), to receive intravenous inebilizumab (300 mg) or identical placebo on days 1 and 15 of the randomised period, which lasted up to 197 days. Participants and all study staff were masked to treatment assignment. The primary endpoint of the randomised period of the trial was time to onset of adjudicated neuromyelitis optica spectrum disorder attack on or before day 197. Participants in the randomised controlled period who had an adjudicated attack, completed 197 days in the study, or were in the randomised controlled period when enrolment stopped, could voluntarily enter the open-label period. In the open-label period, participants either initiated inebilizumab if assigned placebo (receiving 300 mg on days 1 and 15 of the open-label period) or continued treatment if assigned inebilizumab (receiving 300 mg on day 1 and placebo on day 15, to maintain B-cell depletion and masking of the randomised controlled period). All participants subsequently received inebilizumab 300 mg every 6 months for a minimum of 2 years. The end-of-study analysis endpoints were time to adjudicated attack and annualised attack rate (assessed in all participants who received inebilizumab at any point during the randomised controlled period or open-label period [any inebilizumab population] and the aquaporin-4 [AQP4]-IgG seropositive subgroup [any inebilizumab-AQP4-IgG seropositive population]) and safety outcomes (in all participants who were exposed to inebilizumab, analysed as-treated). This study is registered with ClinicalTrials.gov, NCT02200770, and is now complete. FINDINGS: Between Jan 6, 2015, and Sept 24, 2018, 467 individuals were screened, 231 were randomly assigned, and 230 received at least one dose of inebilizumab (n=174) or placebo (n=56). Between May 19, 2015, and Nov 8, 2018, 165 (95%) of 174 participants in the inebilizumab group and 51 (91%) of 56 in the placebo group entered the open-label period (mean age 42·9 years [SD 12·4], 197 [91%] of 216 were female, 19 [9%] were male, 115 [53%] were White, 45 [21%] were Asian, 19 [9%] were American Indian or Alaskan Native, and 19 [9%] were Black or African American). As of data cutoff for this end of study analysis (Dec 18, 2020; median exposure 1178 days [IQR 856-1538], total exposure of 730 person-years) 225 participants formed the any inebilizumab population, and 208 (92%) participants were AQP4-IgG seropositive. Overall, 63 adjudicated neuromyelitis optica spectrum disorder attacks occurred in 47 (21%) of 225 treated participants (60 attacks occurred in 44 [21%] of 208 in the AQP4-IgG seropositive subgroup); 40 (63%) of 63 attacks occurred in 34 (15%) of 225 treated participants during the first year of treatment. Of individuals who had an adjudicated attack while receiving inebilizumab, 36 (77%) of 47 were subsequently attack-free at the end of 4 years. Annualised attack rates decreased year-on-year, with end-of-study adjusted annualised attack rates being similar in the any inebilizumab-AQP4-IgG seropositive subgroup (0·097 [95% CI 0·070-0·14]) and any inebilizumab populations (0·092 [0·067-0·13]). Overall, 208 (92%) of 225 participants who received any inebilizumab had at least one treatment-emergent adverse event, the most frequent of which were urinary tract infection (59 [26%]), nasopharyngitis (47 [21%]), and arthralgia (39 [17%]). Infection rates did not increase over 4 years. Three (1%) of 225 participants in the any inebilizumab population died during the open-label period (one each due to a CNS event of unknown cause and pneumonia, respiratory insufficiency resulting from an neuromyelitis optica spectrum disorder attack and viral pneumonia related to COVID-19), all of which were deemed to be unrelated to treatment. INTERPRETATION: Data from the end-of-study analysis of the N-MOmentum trial showed continued and sustained clinical benefits of long-term inebilizumab treatment in individuals with neuromyelitis optica spectrum disorder, which supports the role of inebilizumab as a CD19+ B-cell-depleting therapy in neuromyelitis optica spectrum disorder. FUNDING: MedImmune and Viela Bio/Horizon Therapeutics, now part of Amgen.
Keywords: Humans; lidé středního věku; neuromyelitis optica; Double-Blind Method; Female; Aged; mladý dospělý; dospělí; výsledek terapie; Neuromyelitis Optica; senioři; lidé; humanizované monoklonální protilátky; dvojitá slepá metoda; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Young Adult; mužské pohlaví